Clinical Aspects and Prognosis Evaluation of Cirrhotic Patients Hospitalized with Acute Kidney Injury - Célio Geraldo de Oliveira Gomes; Marcus Vinicius Melo de Andrade; Ludmila Resende Guedes; Henrique Carvalho Rocha; Roberto Gardone Guimarães; Fernando Antônio Castro Carvalho; Eduardo Garcia Vilela (Canadian Journal of Gastroenterology and Hepatology)
Background. Acute kidney injury occurs in approximately 20% of hospitalized cirrhotic patients. Mortality is estimated at 60% within a month and 65% within a year. Aims. To evaluate survival in 30 days and in 3 months of cirrhotic patients hospitalized with acute kidney injury, identifying factors associated with mortality. Methods. 52 patients with cirrhosis admitted to an academic tertiary center who presented acute kidney injury according to the International Club of Ascites criteria were evaluated. Clinical and laboratory data was collected at diagnosis between 2011 and 2015. Results. Average age was 54.6 (±10.7) years and 69.2% were male. The average MELD, MELD-Na, and Child-Pugh scores were 21.9 (±7.0), 24.5 (±6.7), and 10.1 (±2.2), respectively. Thirty patients (57.7%) were in acute kidney injury stage 1, 16 (30.8%) in stage 2, and six (11.6%) in stage 3. Mortality was 28.6% in 30 days and 44.9% in three months. In multivariate analysis, variables that were associated independently to mortality were lack of response to expansion treatment and Child-Pugh score. Mortality was 93.3% in three months among nonresponders compared to 28.6% among those who responded to volume expansion (p<0.0001). Conclusion. Acute kidney injury in cirrhosis has dire prognosis, particularly in patients with advanced cirrhosis and in nonresponders to volume expansion.